Policy Analysis of the Implementation of Inclusive Schools in Islamic Kindergartens - Andry Setiawan; Hadiansah Hadiansah; Erni Susilawati; Qiqi Yuliati Zaqiah; Supiana Supiana (Journal on Education, 2025)
This study aims to analyse the implementation of inclusive education policies at Brainy Bunch Islamic Kindergarten Bintaro and their impact on the quality of Islamic education. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with the school principal, teachers, and parents, as well as direct field observations. The findings reveal that the inclusive policy at Brainy Bunch Islamic Kindergarten Bintaro has accommodated students from diverse backgrounds, including international students and those with special needs, such as children exhibiting symptoms of ADHD and mild autism. While this policy aligns with Islamic educational values that emphasise diversity and respect for individual rights, its implementation still faces significant challenges, particularly concerning teacher competence, limited facilities, and classroom management. Moreover, the approach adopted by the school is still adaptive and requires further integration with educational theories that support individualised learning, such as Montessori. The study also found that the inclusive policy at Brainy Bunch Islamic Kindergarten Bintaro is not yet fully aligned with national regulations, such as Law No. 8 of 2016 on Disabilities. Therefore, the study emphasises the need for enhanced teacher training, the development of more comprehensive written policies, and the harmonisation of the school’s internal policies with national regulations to create a more inclusive and equitable educational environment.